Pengembangan Keterampilan Sosial Siswa Sebagai Upaya Strategi Guru dalam Pembelajaran PAI di SMA Labschool Palu - Hamid, Abdul (Jurusan Pendidikan IPS, Fakultas Keguruan dan Ilmu Pendidikan Universitas Tadulako, 2022)
This study aims to develop social skills in students at SMA Labschool Palu, and find out the obstacles faced by teachers in developing social skills for students at SMA Labschool Palu. This research uses a qualitative research approach with the type of case study research. Data collection techniques: observation, interview, and documentation techniques which were analyzed by steps, namely data reduction, data presentation, and drawing conclusions. The results showed that developing social skills as a teacher strategy in implementing PAI learning for students in class at SMA Labschool Palu was carried out by: (1) using the 2013 curriculum; (2) using cooperative and contextual learning; (3) providing advice and understanding of anti-social behavior in the learning process; (4) Applying learning rules as limitations in student behavior; (5) apply exemplary nature. There are also obstacles faced by teachers in developing students' social skills at SMA Labschool Palu including: (1) the influence of technology; (2) student personality, (3) family relationship; (3) peer relations, the majority of children learn to develop good social skills by modeling the behavior of their peers.